Lewis Harvey

2021-02-19

Nola Robson

Skilled2021-02-20Added 94 answers

Given that:
$y=\frac{1}{2}x-2$

6x+2y=10

Substutiting the value of y from the first equation into the second equation we get$6x+2y=10\to 6x+2(\left(\frac{1}{2}x\right)-2)=10$

$\to 6x+x-4=10$

$\to 7x=10+4=14$

$\to x=\frac{14}{7}-2$

And hence$y=\left(\frac{1}{2}\right)x-2$

$=\frac{\frac{1}{2}}{2}-2$
=1-2
=-1

Hence the solution of the given equation is x=2, y=-1

6x+2y=10

Substutiting the value of y from the first equation into the second equation we get

And hence

Hence the solution of the given equation is x=2, y=-1

Jeffrey Jordon

Expert2021-08-11Added 2575 answers

Answered on video below